Laura Candler's graphic organizers for reading : teaching tools aligned with the common core - Candler's Laura (Saint Johnsbury, Vermont : Compass, 2012)
A guide for using graphic organizers to incorporate the Common Core Standards for Reading into the classroom. Includes reproducible graphic organizers, charts, and suggested books and texts.
Keywords: Reading (Primary); Reading comprehension -- Problems, exercises, etc; English language -- Composition and exercises